For the Power or the Glory? The Religiosity of America’s Religious Nationalists - Ruiqian Li; Paul Froese (Socius, 2025)
State-centered Christian statism (CS) and society-centered religious traditionalism (RT) are two conservative religious nationalist ideologies that share Christian symbolisms but contain different attitudes about how the state and religion should interact; specifically, CS reflects the belief that Christianity needs to be the guiding ideology of the federal government, and RT mainly promotes the Christian ethos within civil society. We investigate whether these two ideologies predict different forms of religiosity. Analyzing the Baylor Religion Survey (Wave 6), we find that religious believers with stronger agreement with CS show a more self-oriented and petitionary religiosity, in which God is seen as especially interested in and responsive to them. And they tend to pray for divine assistance to meet their personal wants. In contrast, controlling for CS sentiment, believers with stronger RT agreement express a more praise-oriented and confessional religiosity, in which they feel personally accountable for their sins and routinely ask for forgiveness. RT believers also view God as more concerned with the well-being of the whole world and are less likely to ask for personal blessings. These findings further indicate that CS believers tend to express an individualized religiosity and that RT believers are more likely to spread faith and praise God.